2013
DOI: 10.1016/j.psyneuen.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin selectively attenuates rhesus monkeys’ attention to negative facial expressions

Abstract: Intranasal oxytocin (IN-OT) modulates social perception and cognition in humans and could be an effective pharmacotherapy for treating social impairments associated with neuropsychiatric disorders, like autism. However, it is unknown how IN-OT modulates social cognition, its effect after repeated use, or its impact on the developing brain. Animal models are urgently needed. This study examined the effect of IN-OT on social perception in monkeys using tasks that reveal some of the social impairments seen in aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
121
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 50 publications
17
121
3
Order By: Relevance
“…Experiment 3 replicates observations in unrestrained rhesus macaques that intranasal OT blunts orienting toward unfamiliar, emotionally expressive faces displayed in the context of a dotprobe task (24). The present results extend the previous report in two significant ways.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Experiment 3 replicates observations in unrestrained rhesus macaques that intranasal OT blunts orienting toward unfamiliar, emotionally expressive faces displayed in the context of a dotprobe task (24). The present results extend the previous report in two significant ways.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that positive social interactions can reduce social vigilance via OT release, thereby freeing attentional resources for other social and goal-directed behaviors. Thus, our findings resonate with the idea that OT biases global social processes away from negative information and toward positive information (24,26). For example, OT promotes positive implicit associations with in-group members, but has mixed effects on associations with out-group members (7).…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with our findings, a previous study found that intranasally administered OT reduced monkeys' attention to negative facial expressions (fear grin and open-mouth threat), but not to neutral or nonsocial stimuli (24).…”
Section: Ot Reduces Brain Activity Evoked By Negative Emotional Stimulisupporting
confidence: 92%
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 82%
See 1 more Smart Citation